2003
DOI: 10.1080/13576280310001607451
|View full text |Cite
|
Sign up to set email alerts
|

"Where Have All the Students Gone?" Retaining Medical School Graduates through Educational Innovations

Abstract: Self-selected students choosing and participating in early community-based clinical experiences coupled with problem-based learning are more likely to return to the state and to practice primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A total of 30 RCBME programmes were described in the 52 articles included in this review. The majority of RCBME programmes (Table ) were from Australia, and the USA . Other countries represented included Canada, India, Japan, New Zealand, Nigeria, the Philippines, the Solomon Islands and the UK .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 30 RCBME programmes were described in the 52 articles included in this review. The majority of RCBME programmes (Table ) were from Australia, and the USA . Other countries represented included Canada, India, Japan, New Zealand, Nigeria, the Philippines, the Solomon Islands and the UK .…”
Section: Resultsmentioning
confidence: 99%
“…Other countries represented included Canada, India, Japan, New Zealand, Nigeria, the Philippines, the Solomon Islands and the UK . The range of clinical placement durations was wide and extended from two half‐day sessions per week for several years to attachments ranging from 4 weeks to more than 12 months in length, sometimes with repeat visits to a single rural site . The majority of 6–12‐month placements were longitudinal integrated clerkship (LIC) programmes .…”
Section: Resultsmentioning
confidence: 99%
“…25,26 Another study reported a longitudinal clinical experience during preclinical years did not increase students' interest in or selection of a PC career, 21 whereas others were successful. 27,28 Studies conducted prior to the widespread adoption of required FM clerkships found some benefit from ambulatory experiences on PC specialty choice. 29,30 Nonetheless, more recent studies showed no effect.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, curricula that include rural experience at both the undergraduate and graduate levels will contribute to reinforcing the rural practice intentions of physicians and increase the retention rate once a practice is established 14 . Models for such curricula abound 14,16–21 …”
Section: Discussionmentioning
confidence: 99%